Quantifying the impact of clinical coding in chronic kidney disease on risk of death and COVID-19 death - Stuart Stewart; Philip A. Kalra; Evangelos Kontopantelis; Tom Blakeman; George Tilston; Smeeta Sinha (PLoS ONE, 2025)
Background Patients with biochemical evidence of chronic kidney disease (CKD) without a diagnostic code (uncoded CKD) in primary care are at increased risk of death, acute kidney injury (AKI), and unplanned hospital care. Uncoded CKD is highly prevalent and there is no data to evaluate whether patients with uncoded CKD were at an increased risk of COVID-19 death. Aim: to assess whether patients with uncoded CKD stages 3–5 were at increased risk of death and COVID-19 deaths. Methods Descriptive and inferential analyses to measure adjusted hazard of death, and COVID-19 death in patients with CKD stages 3–5 from 2.85 million primary care patients in Greater Manchester, England. Sensitivity analyses using propensity score matching and competing risk regression. Results Coded CKD stages 3 and 4 (versus uncoded) were associated with significantly lower adjusted hazards of death (HR 0.81, CIs 0.77–0.86, p=<0.0001; HR 0.45, CIs 0.34–0.60, p=<0.0001, respectively), and COVID-19 death (HR 0.74, CIs 0.55–0.99, p = 0.03; HR 0.55, CIs 0.30–0.99, p = 0.045, respectively). Descriptive analyses were conducted for patients with CKD stage 5 due to low numbers of patients with uncoded CKD stage 5, precluding survival analyses. Conclusion Our retrospective cohort study suggests that clinical coding is a digital intervention associated with a lower adjusted hazard of death and COVID-19 death in patients with CKD stages 3 and 4, and should be considered a key element in the organisation and delivery of care for people with CKD.